PENERAPAN METODE ROLE PLAYING DIBANTU DENGAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI KALIMAT AJAKAN - aulya putri, ramadhani; Maulida, Salma; Samodra, Touvan Juni; Muskania, Ricka Tesi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve students' learning outcomes in understanding invitation sentences through the implementation of the role-playing method assisted by picture media. The background of this research is based on the low learning outcomes of students in Indonesian language subjects, particularly in the topic of invitation sentences, which is caused by the use of conventional teaching methods without adequate media support. This study employs a classroom action research (CAR) method using the McTaggart model by Kemmis & Nixon, consisting of two cycles. Data were collected through observation, tests, and documentation. The results of the study indicate an improvement in student learning outcomes after the implementation of role-playing assisted by picture media. In the pre-cycle, the percentage of student mastery was only 45.83%, which increased to 62.5% in the first cycle and reached 87.49% in the second cycle. Thus, the role-playing method assisted by picture media is proven to be effective in enhancing students' understanding and learning outcomes in the topic of invitation sentences in Grade II of SDIT Al-Hikmah Pontianak.